DISCURSIVE PRESENTATION OF WOMEN IN THE 2001-2002 AND 2020-2021 MEDIA TEXTS: A CORPUS BASED ANALYSIS - Tsapro, G.; Semeniuk, A. (Studia Philologica, 2021)
This paper is devoted to a corpus based contrastive analysis of the lemma WOMEN in “The Economist” articles published in 2001-2002 and 2020-2021 years. Media discourse is seen as an influential tool which, on the one hand, reflects what is going on in the world, but on the other, influences people’s views on different subjects whether they are political or economic ones forming some specific stereotypical images. Gender stereotypes impose certain behavioural models on men and women prescribing social roles as well as outlining their activities and choices in various social and professional fields. The media in its turn is a reflection of gender marked expectations imposed on both men and women by society. The SketchEngine and LancsBox have been used to process the collocates with WOMEN concentrating mostly on the following ones: empower+WOMEN; encourage+WOMEN; help+WOMEN; WOMEN+take; young+WOMEN; WOMEN+and. The corpus analysis together with critical discourse analysis have been applied to interpret the obtained results with further comparative analysis. The study proves that the way how women are depicted in the news stories have changed greatly over the period of 20 years’ time. The media discourse of recent years offers images when women are empowered, encouraged and helped. Women as active agents with the verb “take” are also depicted in the latest articles. The collocates showing WOMEN’s connections are similar for both corpora, which are MEN and CHILDREN. The most frequently discussed topics of the years 2020-2021 touch upon education, career prospects, relationships, defending personal dignity, becoming more independent; while the media discourse of the beginning of 21st century mostly presents fields of education and work. Young women are shown in troublesome situations in 2001-2002 newspaper articles, whereas 2020-2021 young women demonstrate a confident position in society. The further research perspectives can deal with the study of Ukrainian media discourse, which will enable a contrastive analysis of WOMEN discursive representation in British and Ukrainian newspapers. Keywords: gender, WOMEN, corpus linguistics, media discourse, The Economist.